Promoting Successful College Outcomes for All Students Reply to Weissberg and Owen (2005). [article]. - Robbins, Steven B.
Citing selective evidence does not substitute for meta-analytic findings when examining pootential moderator effects of institutional status and demographic subgroups on psychosocial and study skill predictors of college outcomes. Motivational factors in particular are cebtral to the persistence and performance behavior of all students regardless of institutional and demographic subgroups status. Well-founded and testable hypotheses of institutional and individual difference factors are needed if the authors are to promote greater understanding of how all students can benefit from postsecondary education. --(from the author)